Targeted Nanoparticles for Co-delivery of 5-FU and Nitroxoline, a Cathepsin B Inhibitor, in HepG2 Cells of Hepatocellular Carcinoma - Varshosaz, Jaleh; Fard, Monireh M.; Mirian, Mina; Hassanzadeh, Farshid (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: The first choice of treatment in Hepatocellular Carcinoma (HCC) is 5-fluorouracil (5-FU). Nitroxoline (NIT), a potent inhibitor of Cathepsin B, impairs tumor progression by decreased extracellular matrix degradation. The objective of the current project was designed to target nanoparticles for co-delivery of 5-FU and NIT in order to enhance the 5-FU cytotoxic effects and reduce the metastatic properties of HepG2 cells. Methods: 5-FU and NIT were loaded in chitosan-chondroitin nanoparticles. To target the CD44 receptors of HepG2 cells, Hyaluronic Acid (HA) was conjugated to the chondroitin by adipic acid dihydrazide and the conjugation was confirmed by FTIR and 1HNMR. After physicochemical characterization and optimization of the processing variables, MTT assay was done on HepG2 and NIH3T3 cell lines to determine the cytotoxic properties of HA targeted nanoparticles. Migration of the cells was studied to compare the co-delivery of the drugs with each drug alone. Results: The optimized nanoparticles showed the particle size of 244.7±16.3nm, PDI of 0.30±0.03, drug entrapment efficiency of 46.3±5.0% for 5-FU and 75.1±0.9% for NIT. The drug release efficiency up to 8 hours was about 37.6±0.9% for 5-FU and 62.9±0.7% for NIT. The co-delivery of 5-FU and NIT in targeted nanoparticles showed significantly more cytotoxicity than the mixture of the two free drugs, non-targeted nanoparticles or each drug alone and reduced the IC50 value of 5-FU from 3.31±0.65μg/ml to 0.17±0.03μg/ml and the migration of HepG2 cells was also reduced to five-fold. Conclusion: Co-delivery of 5-FU and NIT by HA targeted chitosan-chondroitin nanoparticles may be promising in HCC.
Keywords: 5-FU